Prevalence and Risk Factors of Medication Errors in Enteral Tube Feeding Among ICU Patients: A Comprehensive Cross-Sectional Analysis - Mansooreh Asghari-Varzaneh; Shirinsadat Badri; Shadi Farsaei (Journal of Research in Pharmacy Practice)
Objective: Most of the patients who are admitted to the intensive care unit (ICU) are forced to feed and use nutrition and medicine through an implanted tube. When administering medication through enteral feeding tubes, it is essential to be cautious, as some drugs may not be suitable due to interactions with feeding formulas or adverse effects when crushed. Some errors during drug gavage can lead to feeding tube blockage, reduced drug effectiveness, or drug toxicity. This study aimed to assess medication errors (MEs) in ICU patients using enteral feeding tubes and identify factors that affect ME incidents. Methods: This descriptive and analytical study was conducted for 9 months in the special care department of hospitals affiliated with Isfahan University of Medical Sciences. It involved 257 patients in the ICU receiving oral medication through an implanted gastric tube. The study assessed the method of oral drug administration, verified the correctness of drug prescriptions, investigated errors in drug provision and administration, and monitored patients for possible side effects of these errors. Demographic information and details about the prescribing physician and relevant nurses were also recorded. Findings: Our findings show that not washing the tube before gavage was the most frequent error (99.6%). However, different factors, whether the patient or the nurse, did not affect them. The other most common errors included mixing drugs simultaneously (75.6%) and not cleaning the tube after administering medication (78.6%). These errors were influenced by factors such as the number of drugs received by the patient, the hospital, and specific shifts. Conclusion: In this study, we found that polypharmacy, the multiplicity of underlying diseases, and nurses’ gender are the most critical factors that increase the number of MEs during the gavage of drugs in patients hospitalized in ICUs.